Enhancing the role of posyandu cadres in early detection and support for high-risk pregnant women through a psychoeducation approach - Meo, Maria Lupita Nena; Rotty, Monique Priscilla Fransiska; Mapaly, Heilbert Armando (Journal of Community Empowerment for Health, 2024)
Introduction: High-risk pregnancies are a major cause of maternal morbidity and mortality, both on a global and national scale. Tuminting Public Health Center, which is a partner in the Community Partnership Empowerment activities, has a significant number of patients with high-risk pregnancies. This indicates an urgent need for the care of high-risk pregnant women. Pregnant women with high-risk pregnancies require priority and continuous care, including early screening/detection, monitoring, and support. However, a situation analysis at the partner site has identified several issues, including: 1) Posyandu cadres are not actively involved in supporting high-risk pregnant women, resulting in these women not receiving appropriate healthcare for their pregnancy conditions. 2) Health promotion media for high-risk pregnant women is limited, preventing these women from receiving accurate health information tailored to their condition.  The objectives of these activities are to enhance the role of cadres in supporting high-risk pregnant women and to improve the availability of health promotion media as a support tool for cadres in their role. Methods: To address these issues, the proposers offer the following solutions: 1) Training on early detection, monitoring, and support for posyandu cadres using a psychoeducational approach.2) Training on the use of digital media for health promotion for high-risk pregnant women for cadres. Results: This training was attended by 37 cadres at Tuminting Public Health Center. Participants' knowledge levels were evaluated before and after the activity.  The evaluation of these activities showed a p-value of 0.000, indicating that there was a difference in the knowledge of the training participants before and after the training. Conclusion: Training activities with a psychoeducational approach can improve the knowledge of cadres, enabling them to enhance their role in early detection and support for high-risk pregnant women.